Volcanoes: a very short introduction, by Michael J. Branney and Jan Zalasiewicz, 2022 - Scarpati, Claudio (Geologos, 2022)
Review: Volcanoes: a very short introduction, by Michael J. Branney and Jan Zalasiewicz, 2022. Oxford University Press, Oxford, UK, 184 pages. Paperback: price €11.06, Kindle: price €5.44, ISBN 978-0199582204.